Financial Development and Economic Growth - Timilsina Susmita (Journal of Corporate Finance Management and Banking System, 2024)
This paper aims to examine the effect of financial developments and economic growth in Nepal employing Autoregressive Distributed lag Model (ARDL) approach of cointegration using the time series data for the period from 1972-2022. Nepal is a unique country for specific case study as it represents the group of landlocked Developing countries and lagging, behind even having lots of natural beauties, and resources within the country. After a recent, significant political shift, Nepal's stable government is currently actively pursuing significant amounts of foreign direct investment. We develop a model with four proxies of financial development (Broad money, Domestic credit by private sectors, Foreign Direct Investment, Gross Capital formation) and econometrically test their contribution in economic growth. And the long bound test suggests that we can reject the null hypothesis of no co-integration and conclude that the variables are co-integrated at all significance levels. Therefore, based on the F-bound test results, we can conclude that there is evidence of co-integration between the variables in the ARDL model.